The Relationship between Work Motivation, Work Discipline and Employee Performance at the Regional Secretariat of Bogor City - Maryani, Yani; Entang, Mohammad; Tukiran, Martinus (International Journal of Social and Management Studies, 2021)
The purpose of this study was to determine the relationship between work motivation and work discipline with employee performance in the Regional Secretariat of Bogor City. The study population was 158 non-leadership employees with ASN status in the Regional Secretariat of Bogor City with 114 non-leadership employees with ASN status calculated using the Slovin formula with an error rate of 5%. Collecting data for each variable studied using a questionnaire with a rating scale. The data analysis technique used descriptive statistical analysis techniques and inferential statistical analysis techniques. The results showed: (a) There is a positive and significant relationship between work motivation and employee performance indicated by the correlation coefficient ry.1 = 0.531 with the degree of strength of the relationship "medium" and Ŷ = 59.707 + 0.531 X1. Work motivation contributes 28.2% to employee performance, (b) There is a positive and significant relationship between work discipline and employee performance as indicated by the correlation coefficient ry.2 = 0.676 with the degree of strength of the relationship "strong" and Ŷ = 27,852 + 0.922 X2 . Work discipline contributes 45.6% to employee performance, and (c) There is a positive and significant relationship between work motivation and work discipline together with employee performance as indicated by the multiple correlation coefficient of ry1.2 = 0.810 with the degree of strength of the relationship. "Very strong" and Ŷ = 49.244 + 0.450X1 + 0.841X2. Work motivation and work discipline together have a 65.6% contribution to employee performance.